The Concept of Strategic Actions and Activities for Development of Hospitality Industry (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In this article is proposed the concept of formation the strategic planning of the hospitality industry development. Strategic planning of hospitality sphere is defined as a set of activities, tasks, material and financial resources, which are aimed for formatting the multi-sectoral model of infrastructure providing the hospitality at the state, region, business entities and the subjects of consumption of its services level. Strategic planning system of hospitality consistsof subjects and objects within sphere of hospitality as a whole, as well as of its infrastructure sectors and within sectors. Interaction the hospitality sphere with other economic sectors is viewed as the interaction with the external environment, while between the hospitality sectors and within them this interaction is within the hospitality sphere and its internal environment. The strategic actions system and activities in the context of the hospitality industrydevelopment is substantiated. There were installed target priorities of the hospitality industry development at the state and regional levels, and also was provided the strategic planning complex at the level of economic hospitality entities.
Keywords: the hospitality sphere, infrastructure sectors, planning, strategic actions and measures, the state and regional management of the hospitality industry, the strategic plans of business entities